NON PHYSICAL LOSS POLICY ON LAND PROCUREMENT FOR GENERAL INTERESTS BASED ON SOCIAL JUSTICE VALUES - Iga Santi (UNISSULA, 2017)
This paper aims to examine non-physical loss in land procurement based on justice value. This study was conducted considering many problems arising from the current phenomenon in which people of Indonesia have not got their rights fairly. Whereas in the mandate of Constitution Article 33 of the 1945 Constitution states that the earth and water and natural resources contained therein are controlled by the state and used for the greatest prosperity of the people. The primary data was obtained from direct interviews with related parties, while secondary data were obtained from literature study. The result shows that people's behavior is strongly influenced by the culture exists in society. The culture of society includes religious values and social values. Government recognition by paying attention to the values in society in the determination of non-physical compensation will prevent prolonged conflicts that occur in the process of land acquisition for the public interest, and there are still many articles that need to be reviewed that immediately review the Article 33 letter f, Article 42 Paragraph 1 jo Article 43 UUPT Year 2012 to better reflect justice for eligible citizens and communities affected by development for the public interest.